Direct detection and characterization of foot‐and‐mouth disease virus in East Africa using a field‐ready real‐time PCR platform. Issue 1 (30th July 2017) - Howson, E. L. A.; Armson, B.; Lyons, N. A.; Chepkwony, E.; Kasanga, C. J.; Kandusi, S.; Ndusilo, N.; Yamazaki, W.; Gizaw, D.; Cleaveland, S.; Lembo, T.; Rauh, R.; et al.
Summary: Effective control and monitoring of foot‐and‐mouth disease (FMD) relies upon rapid and accurate disease confirmation. Currently, clinical samples are usually tested in reference laboratories using standardized assays recommended by The World Organisation for Animal Health (OIE). However, the requirements for prompt and serotype‐specific diagnosis during FMD outbreaks, and the need to establish robust laboratory testing capacity in FMD‐endemic countries have motivated the development of simple diagnostic platforms to support local decision‐making. Using a portable thermocycler, the T‐COR™ 8, this study describes the laboratory and field evaluation of a commercially available, lyophilized pan‐serotype‐specific real‐time RT‐PCR (rRT‐PCR) assay and a newly available FMD virus (FMDV) typing assay (East Africa‐specific for serotypes: O, A, Southern African Territories [SAT] 1 and 2). Analytical sensitivity, diagnostic sensitivity and specificity of the pan‐serotype‐specific lyophilized assay were comparable to that of an OIE‐recommended laboratory‐based rRT‐PCR (determined using a panel of 57 FMDV‐positive samples and six non‐FMDV vesicular disease samples for differential diagnosis). The FMDV‐typing assay was able to correctly identify the serotype of 33/36 FMDV‐positive samples (no cross‐reactivity between serotypes was evident). Furthermore, the assays were able to accurately detect and type FMDV RNA in multiple sample types, including epithelial tissue suspensions, serum, oesophageal–pharyngeal (OP) fluid and oral swabs, both with and without the use of nucleic acid extraction. When deployed in laboratory and field settings in Tanzania, Kenya and Ethiopia, both assays reliably detected and serotyped FMDV RNA in samples ( n  = 144) collected from pre‐clinical, clinical and clinically recovered cattle. These data support the use of field‐ready rRT‐PCR platforms in endemic settings for simple, highly sensitive and rapid detection and/or characterization of FMDV.